An immunoinformatic approach to assessing the immunogenic capacity of alpha-neurotoxins in elapid snake venoms - Chan, Yi Wei; Tan, Choo Hock; Heh, Choon Han; Tan, Kae Yi (Frontiers in Pharmacology, 2023)
Most elapid snakes produce venoms that contain alpha-neurotoxins (α-NTXs), which are proteins that cause post-synaptic blockade and paralysis in snakebite envenoming. However, existing elapid antivenoms are known for their low potency in neutralizing the neurotoxic activity of α-NTXs, while the immunological basis has not been elucidated. In this study, a structure-based major histocompatibility complex II (MHCII) epitope predictor of horse (Equus caballus), complemented with DM-editing determinant screening algorithm was adopted to assess the immunogenicity of α-NTXs in the venoms of major Asiatic elapids (Naja kaouthia, Ophiophagus hannah, Laticauda colubrina, Hydrophis schistosus, Hydrophis curtus). The scoring metric M2R, representing the relative immunogenic performance of respective α-NTXs, showed all α-NTXs have an overall low M2R of <0.3, and most of the predicted binders feature non-optimal P1 anchor residues. The M2R scores correlate strongly (R2=0.82) with the potency score (p-score) generated based on the relative abundances of α-NTXs and the neutralization potency of commercial antivenoms. The immunoinformatic analysis indicates that the inferior antigenicity of α-NTXs is not only due to their small molecular size but also the subpar immunogenicity affected by their amino acid composition. Structural modification with conjugation and synthetic epitope as immunogen may potentially enhance the immunogenicity for improved antivenom potency against α-NTXs of elapid snakes.